Fostering character through stories: Evaluating the effectiveness of a morning story reading program using a mixed-methods approach - Akhyar, Saiful; Artini, Luh Putu; Ramendra, Dewa Putu; Suwastini, Ni Komang Arie (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the effectiveness of character education through a morning story-reading program. The program emphasizes six target values: commitment, respect for others, responsibility, honesty, positive thinking, and togetherness. This research employed a sequential explanatory mixed-method design. It began with a quantitative assessment of the program's effectiveness, followed by a qualitative investigation of students' experiences. Quantitative data were collected via questionnaires and analyzed using descriptive statistics, paired t-tests, and eta squared. Qualitative data were gathered through observations and interviews, analyzed using thematic analysis. The findings indicate that the morning story program significantly impacts students' character development. The questionnaire results, analyzed with paired t-tests, showed a significance level of < 0.05 and an eta squared of 0.74, suggesting a substantial effect. Observations and interviews also revealed that students enjoy the program. This study suggests that the morning story program can be an effective alternative method for fostering students' character development.